Anandamide dysfunction in prodromal and established psychosis - Leweke, F. Markus (Current pharmaceutical design, 2012)
There is epidemiological evidence that frequent cannabis use in general and during puberty in particular increases the risk to suffer psychosis and psychotic symptoms. Based on these observations, there is growing interest in the role of the endogenous cannabinoid system (eCB system) - the point of action for psychoactive cannabinoids - in psychiatric disorders and schizophrenia in particular. It has been hypothesized nearly two decades ago that the eCB system may play a pathophysiological role in schizophrenia either in terms of an endogenous malfunction of the system itself and/or of a secondary malfunction as a result of the use of exogenous cannabinoids like Δ 9-tetrahydrocannabinol, the major psychoactive phytocannabinoid in Cannabis sativa. To test this hypothesis, several studies have been performed investigating endogenous ligands to cannabinoid CB1-receptors such as anandamide both in cerebrospinal fluid and plasma of patients and controls. Here a mini-review of the role of anandamide in schizophrenia is provided.